Analisis Senyawa Metabolit Kunyit (Curcuma longa L.) dan Potensi Bioaktifnya sebagai Antioksidan dan Antiinflamasi dalam Bidang Kesehatan - Shalwa Salsabila S; Ardi Mustakim (CV. Muara Edukasi, 2026)
Turmeric (Curcuma longa L.) contains various bioactive compounds, including phenolic compounds that contribute to antioxidant and anti-inflammatory activities. This study aimed to identify the presence of phenolic compounds in turmeric samples through laboratory testing and to strengthen the findings by comparison with scientific literature. The research method involved the preparation of an experimental solution using 70% ethanol, followed by qualitative identification of phenolic compounds using a 3% FeCl₃ reagent. Color changes observed after the addition of the reagent were used as indicators of phenolic compounds. The laboratory results were analyzed descriptively and compared with findings from previous studies. The results showed that the turmeric sample exhibited a positive reaction to the 3% FeCl₃ test, indicating the presence of phenolic compounds. Comparison with scientific literature supports these findings and confirms the potential of turmeric as a natural source with antioxidant and anti-inflammatory properties for health and pharmaceutical applications